2005
DOI: 10.1128/jvi.79.14.8979-8990.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Replicative Fitness of Primary Human Immunodeficiency Virus Type 1 (HIV-1) Group M, HIV-1 Group O, and HIV-2 Isolates

Abstract: The main (M) group of human immunodeficiency virus type 1 (HIV-1) is responsible for the global AIDS epidemic while HIV-1 group O (outlier) and HIV type 2 are endemic only in west and central Africa. The failure of HIV-2 and especially HIV-1 group O to spread following the initial zoonotic jumps is not well understood. This study was designed to examine the relative replicative capacities between these human lentiviruses. A pairwise competition experiment was performed with peripheral blood mononuclear cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
213
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(226 citation statements)
references
References 60 publications
9
213
2
2
Order By: Relevance
“…Consistent with that study is one that found that HIV-1 group O and HIV-2, which occur at a low frequency worldwide relative to group M HIV-1 isolates, also have reduced replication fitness relative to group M isolates in a multiple-cycle whole-virus assay in PBMCs (6). However, another study demonstrated that subtype C, which is the most common subtype globally, actually has reduced replication fitness compared to subtype B in PBMCs (6,11).…”
Section: Transmission Efficiencysupporting
confidence: 65%
See 2 more Smart Citations
“…Consistent with that study is one that found that HIV-1 group O and HIV-2, which occur at a low frequency worldwide relative to group M HIV-1 isolates, also have reduced replication fitness relative to group M isolates in a multiple-cycle whole-virus assay in PBMCs (6). However, another study demonstrated that subtype C, which is the most common subtype globally, actually has reduced replication fitness compared to subtype B in PBMCs (6,11).…”
Section: Transmission Efficiencysupporting
confidence: 65%
“…However, another study demonstrated that subtype C, which is the most common subtype globally, actually has reduced replication fitness compared to subtype B in PBMCs (6,11). This finding is not consistent with the hypothesis that reduced replication fitness in cell culture correlates with reduced transmission efficiency.…”
Section: Transmission Efficiencycontrasting
confidence: 52%
See 1 more Smart Citation
“…In addition, a previous study reported that subtype D is associated with faster disease progression, rapid CD4 + T cell decline, and a higher rate of treatment failure compared to subtypes A, B, and C 18 . In vitro studies suggested that the replication of subtype C is less competent than that of subtype B 19 . In this study, the mutations related to resistance to ART did not affect clinical features, as most patients (n = 32; 94.7%) showed a good response to HIV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 diversity has an impact on many aspects of HIV infection, including molecular diagnostics [31], cellular tropism [32,33], pathways to drug resistance [34], fitness [35], disease progression [36] and mother-to-child transmission [37]. Despite some limitations, subtype assignment derived from routine drug resistance testing is a fundamental tool for basic surveillance of the spread of HIV-1 clades, with the potential to improve understanding of the biological and clinical features of HIV infection and to enhance prevention strategies.…”
Section: Discussionmentioning
confidence: 99%